Modificación de Probetas de Aluminio Mediante Inmersión en Soles de Zirconio - Fuentes, R.; Rubio, E.; Ramos, E.; Jiménez, S.; Castaño, V. M. (Acta Universitaria, 2001)
It is possible to produce composites by using powder metallurgy and the method called “sol-gel” to obtain composites with aluminum matrix. This method begins compacting aluminum powder, which is then immersed into a colloidal solution of zirconium. By taking advantage of the porosity, the colloidal solution gels along the interconnecting porous, and during the sintering of the pieces, the gel crystallizes in the form of monoclinic and tetragonal zirconia. The introduction of ceramic is like a stiffener and improves the resistance to the wear. The presence of zirconia in the material depends on the conditions of the immersion, and presents a concentration gradient that diminishes in the direction of the center of the piece.
Keywords: Array; Array; Array; Array; Array; Array; Array